Stretch blow molding - Brandau, Ottmar (PDL handbook series, 2012)
Stretch blow molding is the blow molding process used to produce bottles of the strength required for carbonated drinks. In this handbook, Ottmar Brandau introduces the technology of stretch blow molding, explores practical aspects of designing and running a production line and looks at practical issues for quality control and troubleshooting. As an experienced engineer, manager and consultant, Brandau's focus is on optimizing the production process, improving quality and reducing cycle time. This book is a thoroughly practical handbook which provides engineers and managers with the toolkit to improve production and engineering aspects in their own businesses - saving money, increasing output and improving competitiveness by adopting new technologies. . Learn the tricks of the trade from an experienced engineer and manager. . Save money: Practical strategies to optimize the production process, improve quality and reduce cycle times. . Gain knowledge and understanding of the latest technological and best practice developments in stretch blow molding.